IMMIGRANT CITIZENSHIP PROMOTION IN LATVIA’S EDUCATION ENVIRONMENT: STUDENT OPINIONS - Jurgena, Inese; Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
For Latvia as a European Union member state, the issue of immigrant integration into Latvia's society has become currently actuated. Schools have to be ready to enroll pupils of other nationalities and assist them in earlier inclusion into Latvia's society, by promotion of their citizenship development towards the state where they abode, the EU states and the world society in general. The accomplished researches in Latvia reveal that in education environment, it is especially significant to strive for attitude transformation of Latvia's citizens to the inclusion of the immigrant children into Latvia's education environment. Inter-culture experience involvement into the education programmes provides an important factor for the development of citizenship experience in pupils, for their successful integration into another state's society. The aim of the article is: to analyze the situation in education (the accomplished researches) and student opinions on the citizenship development in immigrant children in Latvia's multi-cultural society. The research has implemented the analyses of scientific literature and documents, questionnaire and interviews. The research has come to the conclusion that in education it is significant to evaluate the bilingual, inter-culture and inclusive education for development of citizenship. Exceptional attention has to be paid to preparing the teachers and development of appropriate methodical aids, carrying out of multiple events that can ensure the immigrant opportunities to enrich the capital of Latvia's culture, economy and social life.